1980
DOI: 10.1126/science.207.4437.1309
|View full text |Cite
|
Sign up to set email alerts
|

Yakataga Gap, Alaska: Seismic History and Earthquake Potential

Abstract: A 250-kilometer-long seismic gap in southern Alaska, which is situated along the boundary between the North American and Pacific plates, ruptured in two great earthquakes in 1899. Within the gap, earthquakes of moderate size form a ring of activity around a region of very low seismicity. The number of shocks of magnitude 6 or larger in this ring appears to have increased significantly since the 1958 earthquake, which occurred on the adjacent part of the plate boundary. This space-time pattern is similar to lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…East of the Beringian margin, the transition to ocean‐continent subduction is characterized in the landward half of the fore arc by a region of positive residual free‐air gravity anomalies that is well correlated with the extensively studied Shumagin Islands seismic gap [ Sykes , ; Kelleher et al ., ; McCann et al ., ; Davies et al ., ; Boyd and Jacob , ]. This gap is likely associated with the transition in overthrusting plate structure and is defined by the absence of slip in the 1938 Mw 8.2 earthquake [ Johnson et al ., ] and 1957 Mw 8.7 Andreanof Islands earthquake [ Johnson et al ., ].…”
Section: Fore‐arc Structure: Trench‐parallel Fore‐arc Ridgesmentioning
confidence: 90%
“…East of the Beringian margin, the transition to ocean‐continent subduction is characterized in the landward half of the fore arc by a region of positive residual free‐air gravity anomalies that is well correlated with the extensively studied Shumagin Islands seismic gap [ Sykes , ; Kelleher et al ., ; McCann et al ., ; Davies et al ., ; Boyd and Jacob , ]. This gap is likely associated with the transition in overthrusting plate structure and is defined by the absence of slip in the 1938 Mw 8.2 earthquake [ Johnson et al ., ] and 1957 Mw 8.7 Andreanof Islands earthquake [ Johnson et al ., ].…”
Section: Fore‐arc Structure: Trench‐parallel Fore‐arc Ridgesmentioning
confidence: 90%
“…The Yakataga seismic gap (south coast of Alaska between 140øW and 144øW, Figure 1), the site of collision between the north-northwestward moving Yakutat block and the North American plate, is thought to have a high potential for a major thrust earthquake within the next 20 years [McCann et al, 1980' Jacob, 1984. The gap apparently last ruptured in a sequence of great earthquakes in September 1899.…”
Section: Introductionmentioning
confidence: 99%
“…vations in the preseismic interval might then be extrapolated to suggest that the Chugach-St. Elias fault or one of the subparallel imbricate thrusts represents the greatest seismic hazard in the Yakataga seismic gap. The previous rupture of the Yakataga seismic gap (September 3, 1899[McCann et al, 1980]) is not well enough described that the causative fault can be identified. The coast at Cape Yakataga (near station Furr inFigure 4) was uplifted about 1 m at the time of that earthquake[Tarr and Martin, 1912], but no significant tsunami was reported[Cox and Pararas-Carayannis, 1976].…”
mentioning
confidence: 97%
“…The Yakataga seismic gap (Figure 1), described in detail by McCann et al [1980], has been identified as a region with a high potential for a great earthquake within the next two decades [Jacob, 1984]. The gap is bounded on the west by the rupture area of the 1964 Alaska earthquake (Mw -9.2) and on the east by the 1958 earthquake (Mw = 7.7) on the Fairweather transform fault (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The St. Elias earthquake (Mw = 7.6) ruptured the eastern part of the Yakataga gap in February 1979 (Figure 1). At least part of the gap was previously ruptured in the sequence of great earthquakes that occurred near Yakutat in September 1899 [McCann et al, 1980;Thatcher and Plafker, 1977].…”
Section: Introductionmentioning
confidence: 99%